Evaluation of environmental risk factors associated with survival of generic E. coli in organic integrated crop-livestock systems in California and Minnesota - Sejin Cheong; Carolyn Chandler-Khayd; Sequoia R. Williams; Amélie C. M. Gaudin; Peiman Aminabadi; Michele T. Jay-Russell; Emily Evans; Lee Klossner; Paulo Pagliari; Patricia Millner; Annette Kenney; Fawzy Hashem; et al. (Frontiers in Sustainable Food Systems)
IntroductionIntegrated crop-livestock systems (ICLS) improve soil health and productivity but may lead to the transfer of foodborne pathogens to fresh produce from soil contaminated with the feces of grazing animals.Methods and resultsOver 2 years (2021–2022), organic ICLS field trials were conducted in California (CA) and Minnesota (MN) to examine the presence of foodborne pathogens (Escherichia coli O157, non-O157 Shiga toxin producing E. coli (STEC), and Listeria monocytogenes) across three treatments (fallow, cover crop without grazing, and cover crop with grazing by small ruminants) in soils and produce. A Random Forest (RF) analytical approach was used to determine potential associations between meteorological and soil chemical factors, and the generic E. coli (gEc) presence in soil. The persistence of gEc in soil, as an indicator of fecal contamination, was evaluated using mixed effect zero-inflated negative binomial (ZINB) models, considering top-ranked meteorological factors identified from RF analyses. One produce sample (cucumber) tested positive for non-O157 STEC (0.6%, 1/157) from grazed soil in MN, with no other foodborne pathogens detected in produce. Soil contamination by non-O157 STEC increased in 2022 (2.7%, 15/552) compared to 2021 (0%, 0/504) from both states, aligning with the increased prevalence of non-O157 STEC in post-grazed fecal samples from sheep in CA (41.7%, 5/12) and goats (42.5%, 17/40) in MN in 2022. Concentrations (Most Probable Number/100 g) of gEc in grazed soil returned to levels comparable to non-grazed or fallow treatments within 87–147 days post-graze (DPG) in both years, with a significant decrease predicted after 32 DPG. Interestingly, non-O157 STEC was detected in soil even after concentrations of gEc declined 115–147 DPG.DiscussionAlthough the effects of meteorological factors and soil chemical characteristics were not as influential as treatment or sampling day effects, ZINB analyses with identified meteorological factors in grazed soil suggested that regional differences in gEc counts were likely influenced by maximum air/soil temperatures on the sampling day. Further investigation is needed to evaluate the adoption of the NOP 90-120-day interval rules between manure application by grazing and harvest, considering a wider range of environmental regions and the potential cumulative effect of continuous ICLS in the same field on pathogen loads.